Faktor Penentu dan Keputusan Petani Dalam Memilih Varietas Benih Kedelai di Kabupaten Pidie - Irwan Irwan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. The objective of this research is to understand the factors determining the farmers in selecting the soybean seed and the farmers preference toward soybean. Research was implemented at Indrajaya sub district Pidie Regency. Research method was a survey toward the soybean farmers using a simple random technique, involving total simple of 40 farmers in the 2010 planting season. The result of this research indicates that the dominant factors considered by farmers in selecting soybean seed at Indrajaya sub district were plan age, growth type, plants branching and collapsibility. The factors at Kota Bakti sub district ware price rate, seed shape, selling easiness, plant collapsibility, growth type and plant habit. Farmers preference toward soybean plant was based on the factors considered by farmers. At Indrajaya sub district, the preference was toward the seed with 35-40 days of flowering age, 80-85 days of harvest time, semi-determinate growth type, many branches and collapsibility resistance. At Kota Bakti sub district, the preference was toward those with yellow seed skin color, oval seed shape, determinate growth type, price rate, selling easiness, many branches and Collapsibility resistance.